Immunoglobulins IgG1, IgM and IgA: a synergistic team influencing survival in sepsis. (29th May 2014) - Bermejo‐Martín, J. F.; Rodriguez‐Fernandez, A.; Herrán‐Monge, R.; Andaluz‐Ojeda, D.; Muriel‐Bombín, A.; Merino, P.; García‐García, M. M.; Citores, R.; Gandía, F.; Almansa, R.; Blanco, J.; ,
Abstract: Objective: The impact of endogenous immunoglobulin isotypes on the prognosis of patients with severe sepsis has not been sufficiently explored. The aim of this study was to evaluate the association between immunoglobulin levels in plasma and survival in patients with this condition. Design and patients: A prospective multicentre cohort study was conducted. A total of 172 adult patients admitted to the intensive care unit (ICU) with severe sepsis or septic shock were recruited. Patients were classified based on deciles of immunoglobulin concentrations at diagnosis of sepsis. Categorical variables were created and tested for their association with survival during hospitalization in the ICU. Results: Overall, 42 patients died in the ICU during the study. Kaplan–Meier analysis showed that immunoglobulin concentrations below 300 mg dL −1 for IgG1, 35 mg dL −1 for IgM and 150 mg dL −1 for IgA were associated with shorter survival times. Multivariate regression analysis showed that IgG1 < 300 mg dL −1 was a risk factor for mortality [odds ratio (OR) 2.50, 95% confidence interval (CI) 1.04–6.03; P  = 0.042]. The combined presence of IgG1, IgM and IgA levels below the described thresholds had a synergistic impact on mortality risk (OR 5.27, 95% CI 1.41–19.69; P  = 0.013). A similar effect was observed for combined low levels of IgG1 and IgA (OR 4.10, 95% CI 1.28–13.12; P  =   0.018) and also of IgG1 and IgM (OR 3.10. 95% CI 1.13–8.49; P  =   0.028). Conclusions: The combined presence of low levels of the endogenous immunoglobulins IgG1, IgM and IgA in plasma is associated with reduced survival in patients with severe sepsis or septic shock. Assessment of the concentrations of these immunoglobulins could improve the results of treatment with exogenous immunoglobulins in patients with sepsis.